Peningkatan Keterampilan Proses Sains Menggunakan Metode Eksperimen pada Peserta Didik di SMP Negeri 127 Jakarta - Tyas, Hartining; Astra, I Made (Jurnal Terapan Pendidikan Dasar dan Menengah, 2025)
This classroom action research aims to enhance students’ science process skills (SPS) in Class VIIIA of SMP Negeri 127 Jakarta through the experimental method. Observations indicated low SPS due to teacher-centered learning. Conducted over three cycles, the stages of experimental method are problem identification, hypothesis formulation, experiment design, data collection, analysis, and conclusion. Results showed an increase in the average SPS score from 64 (cycle I) to 82 (cycle III) based observations, supported by worksheet analysis. This Research concludes that the experimental method effectively improves students’ science process skills in learning the topic of Energy.